State of the Global Climate 2024 - World Meteorological Organization (United Nations, 2025)
The publication provides a summary on the state of the climate indicators in 2024 with sections on key climate indicators, extreme events and impacts. The indicators include global temperatures, greenhouse gas concentration, ocean heat content, sea level rise, ocean acidification, Arctic and Antarctic Sea ice, Greenland ice sheet and glaciers and snow cover, precipitation and stratospheric ozone, with an analysis of major drivers of inter-annual climate variability during the year including the El Niño Southern Oscillation and other ocean and atmospheric indices. The highlighted extreme events include those related to tropical cyclones and windstorms, flooding, drought and extreme heat and cold events. The publication also provides most recent finding on climate related risks and impacts including on food security and population displacement.